2017
DOI: 10.1177/0003702817718203
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Real-Time Analysis of Bulk and Bottom Cure of Ultraviolet-Curable Inks Using Fourier Transform Infrared Spectroscopy

Abstract: The curing characteristics of an ultraviolet (UV) ink layer are of utmost importance for the development of UV inks. Measuring either bulk or bottom cure in itself is not new and has been the subject of many articles. In this article, two methods are described based on Fourier transform infrared (FT-IR) spectrometry to measure in real time and simultaneously the bulk and bottom cure of a thin UV ink layer. The procedure consists of applying a thin (10-12 µm) layer of UV-curing ink on an attenuated total reflec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Details about the computation of vinyl-group conversions from the real-time FTIR measurements are provided elsewhere. [23] Eight runs from the described dataset are used for parameter estimation in the current article. The selected runs include three runs with light intensities of 200, 500, and 750 W/m 2 from the first series of experiment, and five runs from the factorial series, whose targeted settings were z f = 8 μm, I l,0 = 1000 W/m 2 , and [BAPO] = 1 or 4 wt.%.…”
Section: Experimental Datamentioning
confidence: 99%
See 3 more Smart Citations
“…Details about the computation of vinyl-group conversions from the real-time FTIR measurements are provided elsewhere. [23] Eight runs from the described dataset are used for parameter estimation in the current article. The selected runs include three runs with light intensities of 200, 500, and 750 W/m 2 from the first series of experiment, and five runs from the factorial series, whose targeted settings were z f = 8 μm, I l,0 = 1000 W/m 2 , and [BAPO] = 1 or 4 wt.%.…”
Section: Experimental Datamentioning
confidence: 99%
“…Details about the computation of vinyl‐group conversions from the real‐time FTIR measurements are provided elsewhere. [ 23 ]…”
Section: Experimental Datamentioning
confidence: 99%
See 2 more Smart Citations
“…[31] For consistency, the results for the polymerization of the pure phase in a thin film were referenced against other HDDA studies that underwent different photoinitiation treatments but showed the same reaction kinetics, e.g., in dynamic photo-calorimetry scans with other photo-initiators. [32][33][34] Experimental section…”
Section: Graphical Abstract Introductionmentioning
confidence: 99%